2020
DOI: 10.3390/cancers12092690
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1 Repression Potentiates Radiation Effectiveness by Downregulating G3BP2 Expression and Promoting the Activation of TXNIP-Related Pathways in Oral Cancer

Abstract: Radiotherapy is commonly used to treat oral cancer patients in the current clinics; however, a subpopulation of patients shows poor radiosensitivity. Therefore, the aim of this study is to identify a biomarker or druggable target to enhance the effectiveness of radiotherapy on oral cancer patients. By performing an in silico analysis against public databases, we found that the upregulation of FOXD1, a gene encoding forkhead box d1 (Foxd1), is extensively detected in primary tumors compared to normal tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Our FOXD1 results were consistent with Perri et al, (2017) and Lin et al, (2020) results showing upregulation of FOXD1 expression in oral squamous cell carcinoma cell lines. Furthermore, the study heavily suggested that FOXD1 would most probably play a key role during the OSCC tumorigenesis, delineating it as a novel diagnostic and prognostic biomarker for OSCC that is closely related to tumor invasion and metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Our FOXD1 results were consistent with Perri et al, (2017) and Lin et al, (2020) results showing upregulation of FOXD1 expression in oral squamous cell carcinoma cell lines. Furthermore, the study heavily suggested that FOXD1 would most probably play a key role during the OSCC tumorigenesis, delineating it as a novel diagnostic and prognostic biomarker for OSCC that is closely related to tumor invasion and metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…FOXD1, a transcription factor, has been found to regulate the expression of genes downstream by directly binding to their promoters. In oral cancer cells, FOXD1 promotes the malignant progression of cells by upregulating G3BP2 expression via directly binding to its promoter (Lin et al 2020 ). As previously reported, DKK1 is upregulated in glioma cells and tissues, which is similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…FOXD1 expression is upregulated in several types of cancers [ 46 ]. Moreover, the knockdown of FOXD1 impairs the colony-forming abilities of oral cancer cells after radiation treatment [ 47 ]. Another study showed that upregulated FOXD1 contributed to melanoma cells’ resistance to vemurafenib via the recruited expression of connective tissue growth factor [ 48 ].…”
Section: Discussionmentioning
confidence: 99%